PENGARUH PERSENTASE PEMBERIAN RANSUM PADA SIANG DAN MALAM HARI TERHADAP BOBOT HIDUP, BOBOT KARKAS, DAN BOBOT GIBLET AYAM PETELUR JANTAN TIPE MEDIUM DI KANDANG PANGGUNG - Cintia Agustin Patria (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2017)
This study aimed at evaluating the effect of feeding time system and percentage on body weight, carcass and giblets of layers males. Two hundred and eighty eight 3 weeks old male layers were rearing and randomly distributed on three groups (R1, R2, and R3). R1 were feeding 30% during the day and 70% at night, R2 were feeding 50% during the day and 50% at night, R3 were feeding 70% during the day and 30% at night. Body weight, carcass weight and giblet weight were not significanly affected (P>0.05) by all of feeding time system and percentage. Keyword : Body weight, carcass, giblet feeding Time.